Recent investigations in the Province of Lori - Herles, Michael; Davtyan, Ruben (ARAMAZD: Armenian Journal of Near Eastern Studies, 2020)
Since 2016 an Armenian-German team has been resuming surveys in the province of Lori. After extensive surveys in the two northern districts of Stepanavan and Tashir in 2016, corresponding explorations were conducted in the southern districts of Spitak and Gugark in the following year 2017. In the eastern district of Tumanian our team has hardly done any work up to date. During the two surveys of 2016 and 2017, a total of 52 sites (Figure 1) were inspected, twelve of which are located in the district of Stepanavan, eleven in the district of Tashir, 19 in the district of Spitak, nine the district of Gugark, and one in the district of Tumanian. All sites bear a serial number with the abbreviation LS (= Lori Survey) and are listed in the appendix of this report.